Rapid Screening for Cognitive Impairment in Parkinson’s Disease: A Pilot Study - YanHong Dong; Way Inn Koay; Leonard Leong Litt Yeo; Christopher Li-Hsian Chen; Jing Xu; Raymond Chee Seong Seet; Erle Chuen Hian Lim (Parkinson's Disease)
Aim. This study sought to establish the discriminant validity of a rapid cognitive screen, that is, the National Institute of Neurological Disease and Stroke-Canadian Stroke Network (NINDS-CSN) 5-minute protocol, and compare its discriminant validity to the Montreal Cognitive Assessment (MoCA) and Mini Mental State Examination (MMSE) in detecting cognitive impairment (CI) in PD patients. Methods. One hundred and one PD patients were recruited from a movement disorders clinic in Singapore and they received the NINDS-CSN 5-minute protocol, MoCA, and MMSE. No cognitive impairment (NCI) was defined as Clinical Dementia Rating (CDR) = 0 and CI was defined as CDR ≥ 0.5. Results. Area under the receiver operating characteristic curve of NINDS-CSN 5-minute protocol was statistically equivalent to MoCA and larger than MMSE (0.86 versus 0.90, P=0.07; 0.86 versus 0.76, P=0.03). The sensitivity of NINDS-CSN 5-minute protocol (<9) was statistically equivalent to MoCA (<22) (0.77 versus 0.85, P=0.13) and superior to MMSE (<24) (0.77 versus 0.52, P<0.01) in detecting CI, while the specificity of NINDS-CSN 5-minute protocol (<9) was statistically equivalent to MoCA (<22) and MMSE (<24) (0.78 versus 0.88, P=0.34). Conclusion. The NINDS-CSN 5-minute protocol is time expeditious while remaining statistically equivalent to MoCA and superior to MMSE and therefore is suitable for rapid cognitive screening of CI in PD patients.